Novel human melanoma brain metastasis models in athymic nude fox1nu mice: Site‐specific metastasis patterns reflecting their clinical origin. (6th October 2021) - Svendsen, Henrik A.; Meling, Torstein R.; Nygaard, Vigdis; Waagene, Stein; Russnes, Hege; Juell, Siri; Rogne, Siril G.; Pahnke, Jens; Helseth, Eirik; Fodstad, Øystein; Mælandsmo, Gunhild M.
Abstract: Background: Malignant melanomas frequently metastasize to the brain, but metastases in the cerebellum are underrepresented compared with metastases in the cerebrum. Methods: We established animal models by injecting intracardially in athymic nude fox1 nu mice two human melanoma cell lines, originating from a cerebral metastasis (HM19) and a cerebellar metastasis (HM86). Results: Using magnetic resonance imaging (MRI), metastases were first detected after a mean of 34.5 days. Mean survival time was 59.6 days for the mice in the HM86 group and significantly shorter (43.7 days) for HM19‐injected animals ( p < 0.001). In the HM86 group, the first detectable metastasis was located in the cerebellum in 15/55 (29%) mice compared with none in the HM19 group ( p < 0.001). At sacrifice, cerebellar metastases were found in 34/55 (63%) HM86‐injected mice compared with 1/53 (2%) in the HM19‐injected ( p < 0.001) mice. At that time, all mice in both groups had detectable metastases in the cerebrum. Comparing macroscopic and histologic appearances of the brain metastases with their clinical counterparts, the cell line‐based tumors had kept their original morphologic characteristics. Conclusions: The present work demonstrates that human brain‐metastatic melanoma cells injected intracardially in mice had retained inherent characteristics also in reproducing interaction with subtle microenvironmental brain tissue compartment‐specific features. The models offer new possibilities for investigating tumor‐ and host‐associated factors involved in determining tissue specificity of brain metastasis. Abstract : We present two new models that offer novel possibilities for investigating tumor‐ and host‐associated factors involved in malignant melanoma brain metastasis in general and tissue‐specific metastasis in particular. Two cell lines derived from a cerebral and a cerebellar human‐brain metastasis gave rise to two completely different patterns of spread, where 62.9% of animals injected with the cell line derived from a cerebellar human metastasis developed cerebellar metastases compared with 2% in the group injected with the cerebral cell line.